Validity of Problem Based Learning Oriented E-LAPD to Improve Chemical Literacy Skills of High School Students - Febriningtyas, Siti Amelia; Dwiningsih, Kusumawati (Jurnal Paedagogy, 2024)
This study aims to produce valid Problem Based Learning (PBL) oriented E-LAPD to improve students' chemical literacy skills on acid-base material. This research method used development research with the 4D model which includes define, design, develop, and disseminate. However, it is limited to the development stage. The subjects of this study were phase F students of class XI SMAN 1 Krembung Sidoarjo as many as 36 students. The research instrument used in collecting data was a validation sheet. Data analysis techniques in this study used quantitative analysis techniques through the provision of validation questionnaires to validators. The results of this study indicated that the Problem Based Learning (PBL) oriented E-LAPD to improve students' chemical literacy skills on acid-base material was declared feasible to use because it got a mode score of 4 with valid criteria based on content and construct validity which includes aspects of language, presentation, and graphics.